2016
DOI: 10.3389/fnbeh.2016.00234
|View full text |Cite
|
Sign up to set email alerts
|

Slips of Action and Sequential Decisions: A Cross-Validation Study of Tasks Assessing Habitual and Goal-Directed Action Control

Abstract: Instrumental learning and decision-making rely on two parallel systems: a goal-directed and a habitual system. In the past decade, several paradigms have been developed to study these systems in animals and humans by means of e.g., overtraining, devaluation procedures and sequential decision-making. These different paradigms are thought to measure the same constructs, but cross-validation has rarely been investigated. In this study we compared two widely used paradigms that assess aspects of goal-directed and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 76 publications
(155 reference statements)
2
44
1
Order By: Relevance
“…In the current study, we aimed to address the two issues raised above by including (1) more highly obese individuals to boost the contrast between groups, and (2) an intermediate overweight group for more sensitivity to detect the existence of potential linear or quadratic relationships between weight status and behavioural control. The original two-step task was implemented to disentangle and directly compare the reliance on model-based and model-free control 16 , 25 , 30 . We hypothesized that weight status relates to the degree to which individuals rely on model-based and model-free learning, and that it may do so in a linear or quadratic manner.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we aimed to address the two issues raised above by including (1) more highly obese individuals to boost the contrast between groups, and (2) an intermediate overweight group for more sensitivity to detect the existence of potential linear or quadratic relationships between weight status and behavioural control. The original two-step task was implemented to disentangle and directly compare the reliance on model-based and model-free control 16 , 25 , 30 . We hypothesized that weight status relates to the degree to which individuals rely on model-based and model-free learning, and that it may do so in a linear or quadratic manner.…”
Section: Introductionmentioning
confidence: 99%
“…Both studies found that model-based learning was a positive predictor of flexible adjustments based on a change in outcome value (i.e., goal-directedness), whereas model-free learning was unrelated to performance on the outcome-devaluation task. Relatedly, a recent study found that performance on the SOAT showed a moderately positive correlation with model-based learning on the two-step task, but once again, bore no relation with model-free learning ( Sjoerds et al, 2016 ). Taken together, these studies are consistent with the notion that model-based reinforcement learning is a good approximation of goal-directed control defined in terms of performance on outcome-devaluation tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Second, there is some debate on whether – and to what extent – model-free learning maps on to traditional definitions of habitual control (Miller et al, 2019; see also Gillan et al, 2015; Sjoerds et al, 2016). Miller et al (2019) argue that traditional conceptualizations of habits reflect stimulus-response associations devoid of expected value representations (i.e., are value-free ), whereas model-free algorithms still depend on the expected value representations associated with a learner’s available actions (i.e., are value-based ).…”
Section: Discussionmentioning
confidence: 99%